2018
DOI: 10.1111/ppc.12329
|View full text |Cite
|
Sign up to set email alerts
|

Drawing forward family strengths in short therapeutic conversations from a psychiatric nursing perspective

Abstract: Purpose The aim of the narrative is to describe the therapeutic process and experience from a psychiatric nursing perspective, in therapeutic communication, with a father and his son in acute psychiatry. Methods In this case scenario, the Family Strength‐Oriented Therapeutic Conversation Intervention (FAM‐SOTC Intervention) was used. Findings The FAM‐SOTC Intervention was found to be beneficial for the father‐son relationship. Practice Implication It is encouraging for nurses in acute psychiatry to know that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…Rather, they tended to shift the discussion to issues related to the provision of care. Thus these clinically reported findings underline the significance of offering family-centred support conversations as a supplement to other treatment in the community mental health service, and to demonstrate that this might ease the families' burden, guilt and distress (Sveinbjarnardottir & Svavarsdottir, 2019).…”
Section: Health Professionals' Perceptions Of Quality In Psychiatric mentioning
confidence: 53%
See 1 more Smart Citation
“…Rather, they tended to shift the discussion to issues related to the provision of care. Thus these clinically reported findings underline the significance of offering family-centred support conversations as a supplement to other treatment in the community mental health service, and to demonstrate that this might ease the families' burden, guilt and distress (Sveinbjarnardottir & Svavarsdottir, 2019).…”
Section: Health Professionals' Perceptions Of Quality In Psychiatric mentioning
confidence: 53%
“…This can create feelings of alienation in families with regard to involvement in care. Thus, a positive attitude from the mental health professionals regarding family care involvement is of great importance in ensuring that each family member and the family as a whole are offered high quality of care (Sveinbjarnardottir & Svavarsdottir, 2019). This is important as patients' (or family members') experiences of high quality of care are reported to be associated with improved treatment outcomes and improved quality of life (Blenkiron & Hammill, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that mental health care professionals build trustful relationships with the patient and family members, framing family support conversations as a safe arena. Sveinbjarnardóttir and Svavarsdóttir (2019) assert that mental health care professionals who have the knowledge, training, and capacity to build a partnership with the family as the unit of care can improve patient services.…”
Section: Discussionmentioning
confidence: 99%
“…Intervention studies with patients and family members in acute psychiatric hospital units, who received family nursing conversations focused on family strengths, reported that family members perceived significant higher emotional and cognitive support after the intervention (Sveinbjarnardóttir et al, 2013). In addition, benefits were observed in families of young people living with severe mental illness regarding revisiting and building new connections among family members, and strengthening and supporting the family network (Sveinbjarnardóttir & Svavarsdóttir, 2019). These family nursing intervention studies were guided by the CFAM and CFIM and/or the IBM as the theoretical framework to inform the interventions offered (Gísladóttir et al, 2017; Gísladóttir & Svavarsdóttir, 2017; Svavarsdóttir et al, 2019; Sveinbjarnardóttir et al, 2013; Sveinbjarnardóttir & Svavarsdóttir, 2019).…”
Section: Intervention Studies: Families Living With Mental Illnessmentioning
confidence: 99%
“…Similarly Moore and McQuestion (2012) have stressed that APNs provide service where gaps exist in health care systems. APNs provide high-quality care by offering evidence-based information and recommendations through support, advocacy, and care coordination (Kamban & Svavarsdottir, 2013; Konradsdottir & Svavarsdottir, 2013; Moore & McQuestion, 2012; Svavarsdottir & Gisladottir, 2019; Sveinbjarnardottir & Svavarsdottir, 2019; Wright, 2015).…”
Section: Introductionmentioning
confidence: 99%